Joint Carrier Phase Estimation and Data Detection Algorithms for Multi-h CPM Data Transmission - Liebetreu, J. (I.R.E. transactions on communications systems, 1986)
A dynamic programming algorithm, developed in [1]-[4] for obtaining the joint estimate of carrier phase and data, is applied to multi h continuous phase modulation. A MAP estimator detects data and jointly tracks carrier phase consisting of a normal random walk phase jitter process. Monte Carlo computer simulations are used to evaluate the probability of error performance for two receivers employed in demodulation of multi- h CPM signals. A simplified algorithm is proposed which yields up to a tenfold reduction in computation time at the expense of less than 1 dB in signal-to-noise ratio at the error rates computed, and for suitable ranges of phase jitter increments variance.